SOIL QUALITY AND HEIGHT DIAMETER MODEL ASSESSMENT IN THE MANAGEMENT OF GMELINA ARBOREA PLANTATION IN NASARAWA STATE UNIVERSITY, NIGERIA - Clement, Segun A.; Soba, T. M.; Balogun, P. B. (FUDMA Journal of Sciences, 2023)
Gmelina arborea is a very important timber species as it provides wood for furniture, serves as carbon sink and creates micro-climate with decrease soil temperatures enabling smaller niches to be formed within the forest ecosystem. Also, the nutrients composition of forest soil determines its stand structure and composition, growth rate and dominance, including other silvicultural practices. The study assessed soil quality and height-diameter (H-D) models in the management of Gmelina arborea plantation in Nasarawa State University. Thirty (30) temporary sample plots of 0.01 ha size were randomly selected from the sampling frame with 30% sampling intensity. Thereafter, the total height and the Dbh of each tree within the selected plots was measured for height-diameter model assessment. Also, ten (10) soil samples were randomly collected from the thirty (30) selected plots for H-D modeling in order to assess the soil properties of the plantation. Soil samples obtained were analyzed in the Faculty of Agriculture Laboratory to obtain data and further subjected to statistical analysis. The results of height-diameter models revealed that model one (1) with Akaike Information Criterion (62.19), Bayesian Information Criterion (66.39) and Residual Standard Error (0.64) had the lowest model selection indices when compared with other four models applied. Therefore, model one (1) was selected as the best and grand model for Gmelina aborea plantation in the study area. Also, the result of soil quality showed a significant difference between the soil properties in the study area. The Least Significant Difference result also showed that...